Differential glycosylation of collagen modulates lung cancer stem cell subsets through β1 integrin‐mediated interactions. Issue 1 (10th November 2020) - Gardelli, Cecilia; Russo, Laura; Cipolla, Laura; Moro, Massimo; Andriani, Francesca; Rondinone, Ornella; Nicotra, Francesco; Sozzi, Gabriella; Bertolini, Giulia; Roz, Luca
Abstract: In lung cancer, CD133+ cells represent the subset of cancer stem cells (CSC) able to sustain tumor growth and metastatic dissemination. CSC function is tightly regulated by specialized niches composed of both stromal cells and extracellular matrix (ECM) proteins, mainly represented by collagen. The relevance of collagen glycosylation, a fundamental post‐translational modification controlling several biological processes, in regulating tumor cell phenotype remains, however, largely unexplored. To investigate the bioactive effects of differential ECM glycosylation on lung cancer cells, we prepared collagen films functionalized with glucose (Glc‐collagen) and galactose (Gal‐collagen) exploiting a neoglycosylation approach based on a reductive amination of maltose and lactose with the amino residues of collagen lysines. We demonstrate that culturing of tumor cells on collagen determines a glycosylation‐dependent positive selection of CSC and triggers their expansion/generation. The functional relevance of CD133+ CSC increase was validated in vivo, proving an augmented tumorigenic and metastatic potential. High expression of integrin β1 in its active form is associated with an increased proficiency of tumor cells to sense signaling from glycosylated matrices (glyco‐collagen) and to acquire stemness features. Accordingly, inhibition of integrin β1 in tumor cells prevents CSC enrichment, suggesting that binding of integrin β1 to Glc‐collagen subtends CSC expansion/generation. We provide evidence suggesting that collagen glycosylation could play an essential role in modulating the creation of a niche favorable for the generation and selection/survival of lung CSC. Interfering with this crosstalk may represent an innovative therapeutic strategy for lung cancer treatment. Abstract : Glycans are well known for their involvement in recognition phenomena between cells; however, the role of small glycan epitopes in cell–extracellular matrix (ECM) interactions needs to be further elucidated. Here we exploit bioactive ECM mimetics, functionalizing type I collagen films with different glycans, to investigate the relevance of specific ECM glycosignatures in tumor‐ECM interactions. We show that in vitro culturing of lung cancer cells on glycosylated collagen films results in differential modulation of cancer stem cells (CSC), associated in vivo with an enhanced tumor initiation ability and increased metastatic potential. Interactions of CSC with glycosylated collagen are regulated through the active form of integrin β1. Interfering with integrin β1 signaling results in abrogation of CSC enrichment induced by glycosylated collagen.